2015
DOI: 10.1016/j.cell.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Rho1 Activity Regulate Neuronal Plasticity and Network Hierarchy

Abstract: Summary Neuronal plasticity helps animals learn from their environment. However, it is challenging to link specific changes in defined neurons to altered behavior. Here we focus on circadian rhythms in the structure of the principal s-LNv clock neurons in Drosophila. By quantifying neuronal architecture, we observed that s-LNv structural plasticity changes the amount of axonal material in addition to cycles of fasciculation and defasciculation. We found that this is controlled by rhythmic Rho1 activity that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
146
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(154 citation statements)
references
References 47 publications
7
146
1
Order By: Relevance
“…For example, in the moth Manduca sexta , odorant-induced ORN activity appears after the development of the 64 glomeruli (Oland and Tolbert, 1996) and thus, is unlikely to play a role. Therefore, the orco phenotype in ants might be one of the first examples of activity-driven patterning in insects (Petsakou et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For example, in the moth Manduca sexta , odorant-induced ORN activity appears after the development of the 64 glomeruli (Oland and Tolbert, 1996) and thus, is unlikely to play a role. Therefore, the orco phenotype in ants might be one of the first examples of activity-driven patterning in insects (Petsakou et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Toy then activates transcription of Pura , a “plasticity gene” which encodes a Rho1 GEF that increases Rho1 activity and helps retract s-LN v projections to reduce their signaling potency (Fig. 6) (Petsakou et al, 2015). Although many of our experiments used the mammalian Kir2.1 channel to induce hyperpolarization, the Pura transcriptional reporter normally shows a 24hr rhythm in LN v s and can also be induced via an inhibitory neural circuit.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of pacemaker neurons – the 4 small ventral lateral neurons (s-LN v s) in each brain hemisphere – show predictable and intrinsic daily rhythms in their excitability (Cao and Nitabach, 2008) and in the structure of their projections (Cao and Nitabach, 2008; Fernandez et al, 2008). We recently showed that Rho1 activity is rhythmic in s-LN v projections and this is regulated by rhythmic expression of Puratrophin-like ( Pura ), a Rho1 Guanine nucleotide exchange factor (GEF) that increases Rho1 activity (Petsakou et al, 2015). s-LN v plasticity is also regulated by neuronal activity, which normally peaks around dawn (Cao and Nitabach, 2008) when s-LN v projections are maximally expanded.…”
Section: Introductionmentioning
confidence: 99%
“…We have also combined transgenic RNAi with the inducible GAL80 ts system (McGuire et al, 2003), similar to approaches used in several previous Drosophila studies (Duvall and Taghert, 2012; Zhang et al, 2013; Petsakou et al, 2015). Our behavior and expression data indicate that GAL80 ts is very effective at suppressing da GAL4 activity at 19°C but ineffective at 29°C, although minor decreases in NA expression levels in the 19°C – 19°C condition ( Figure 4A ) could reflect some leakiness of the system.…”
Section: Discussionmentioning
confidence: 99%